THE PRIVATISATION AND THE ECONOMICAL ENVIRONMENT OF ARGES COUNTY - Cristina, CHIRIAC (Strategii Manageriale)
The privatisation process has generated over time a lot of controversial opinions of the specialists. The lack of a complete analysis of the privatisation process, even now, after more than 20 years from its beginning, has raised questions regarding the accomplishment of the goals of the macro-economic policy. This paper aims to enclose the analysis and evaluation function of the privatisation process in Arges County. Based on the information gathered, we will analyse individually the privatised companies in Arges County, we will try to estimate the success rate of the privatisation process but also what were the effects of the privatisation process with regards to employment. The purpose of this paper is the improvement of the evaluation frame of the privatisation process by creating an inventory of problems and techniques, establishing the success rate and the percent of failed privatisations. This is a complex subject whose causes and effects are connected in the Romanian context, sometimes in the European and even geopolitical one, as we will try to prove by analysing the most important privatised companies from Arges County: Automobile Dacia SA and ARO SA.